Immune therapy in colorectal cancer. (November 2017) - Lapeyre-Prost, Alexandra; Terme, Magali; Pernot, Simon; Marcheteau, Elie; Pointet, Anne-Laure; Voron, Thibault; Tartour, Eric; Taieb, Julien
The evidence that the immune system, when rightly stimulated, can eradicate cancer cells, combined with the latest knowledge about antitumor immunity, has led to recent progress in cancer immunotherapy. While infiltration of tumors with immune cells is described in advanced stage colorectal cancer (CRC), the first data concerning the clinical efficacy of immune-targeted therapies in CRC patients were disappointing. The evidence of tumor responses in CRC patients with microsatellite instability treated with immune checkpoint blockers has renewed the interest for research in the field of CRC immunotherapy. In this article, we briefly review the role of T lymphocytes infiltrating CRC tumors in order to introduce a brief history of CRC immunotherapy and then current trials involving immune-based strategies and particularly immune checkpoint blockers.